2017
DOI: 10.1002/ana.24901
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome in human neurological disease: A review

Abstract: Almost half the cells and 1% of the unique genes found in our bodies are human, the rest are from microbes, predominantly bacteria, archaea, fungi, and viruses. These microorganisms collectively form the human microbiota, with most colonizing the gut. Recent technological advances, open access data libraries, and application of high-throughput sequencing have allowed these microbes to be identified and their contribution to neurological health to be examined. Emerging evidence links perturbations in the gut mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
301
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 437 publications
(308 citation statements)
references
References 140 publications
(462 reference statements)
3
301
0
4
Order By: Relevance
“…This so-called ‘gut-brain axis’ is believed to link functions of the brain with peripheral intestinal functions 2. Especially, unbalances in the intestinal microbiome in relation to neurological diseases have recently taken the spotlight, with studies relating PD with a more proinflammatory gut milieu 21. Recent evidence for the gut as an initial site of PD pathology comes from a study by Sampson et al demonstrating the importance of the gut microbiota to the pathophysiology of neuroinflammation in the development of motor deficits in the α-syn-overexpressing mouse 22.…”
Section: Discussionmentioning
confidence: 99%
“…This so-called ‘gut-brain axis’ is believed to link functions of the brain with peripheral intestinal functions 2. Especially, unbalances in the intestinal microbiome in relation to neurological diseases have recently taken the spotlight, with studies relating PD with a more proinflammatory gut milieu 21. Recent evidence for the gut as an initial site of PD pathology comes from a study by Sampson et al demonstrating the importance of the gut microbiota to the pathophysiology of neuroinflammation in the development of motor deficits in the α-syn-overexpressing mouse 22.…”
Section: Discussionmentioning
confidence: 99%
“…An early study found that subgingival microbiome is associated with changes in cognitive function (Cockburn et al, 2012). Please refer to Pistollato et al (2016) and Tremlett, Bauer, Appel‐Cresswell, Finlay, and Waubant (2017) as a starting point.…”
Section: Systems Level Events In Aging and Admentioning
confidence: 99%
“…Increased gut permeability may enable microbes or microbial metabolites to enter the bloodstream (reviewed in Tremlett et al [16]). Further, gut microbes produce neuromodulating metabolites (e.g., short chain fatty acids) and can induce the production of neurotransmitters such as serotonin and neuromodulating hormones such as peptide YY.…”
Section: Multiple Sclerosismentioning
confidence: 99%